2023
DOI: 10.1111/all.15667
|View full text |Cite
|
Sign up to set email alerts
|

EAACI guidelines on environmental science in allergic diseases and asthma – Leveraging artificial intelligence and machine learning to develop a causality model in exposomics

Abstract: Allergic diseases and asthma are intrinsically linked to the environment we live in and to patterns of exposure. The integrated approach to understanding the effects of exposures on the immune system includes the ongoing collection of large‐scale and complex data. This requires sophisticated methods to take full advantage of what this data can offer. Here we discuss the progress and further promise of applying artificial intelligence and machine‐learning approaches to help unlock the power of complex environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 95 publications
0
18
0
2
Order By: Relevance
“…In the context of allergic diseases, AI can potentially support unbiased patient characterization based on their endotypes and more accurately predict responders and non‐responders to targeted interventions or immune‐modulating therapies. By uncovering novel biomarkers and identifying subgroups of patients with distinct immunological profiles, AI can facilitate the development of personalized treatment strategies (biologicals and small molecules/allergen immunotherapy and other immune‐modulatory interventions), ultimately improving patient outcomes and achieving disease modification and targeted prevention 19 …”
Section: Introductionmentioning
confidence: 99%
“…In the context of allergic diseases, AI can potentially support unbiased patient characterization based on their endotypes and more accurately predict responders and non‐responders to targeted interventions or immune‐modulating therapies. By uncovering novel biomarkers and identifying subgroups of patients with distinct immunological profiles, AI can facilitate the development of personalized treatment strategies (biologicals and small molecules/allergen immunotherapy and other immune‐modulatory interventions), ultimately improving patient outcomes and achieving disease modification and targeted prevention 19 …”
Section: Introductionmentioning
confidence: 99%
“…Unsupervised clustering of large sIgE datasets allowed the identification of a group of participants with the highest burden by their sensitization patterns. Multifaceted computation‐based methods may in future lead to a more targeted clinical supervision of patients 49,50 …”
Section: Discussionmentioning
confidence: 99%
“…Multifaceted computation-based methods may in future lead to a more targeted clinical supervision of patients. 49,50 A recent study on 9 childhood cohorts showed sensitization in the context of regionality. IgE profiles varied depending on the geographical exposome of participants.…”
Section: Participants' Ige Signature Complexity Correlated With Socio...mentioning
confidence: 99%
“…AI's ability to handle complex data and continuously learn from it accelerates the discovery of novel treatments and therapies, ultimately enhancing the quality of care for allergy sufferers and contributing to the advancement of allergy research. 3 Tens of new AI tools are being introduced to our lives every week. The rapid growth of AI tools is transforming how we live and work.…”
Section: F I G U R E 1 Structure Of Artificial Intelligence (Ai) (A)mentioning
confidence: 99%
“…Moreover, AI can be used to develop predictive models that forecast the prevalence and severity of allergies in specific populations, potentially enabling better resource allocation and public health planning. AI's ability to handle complex data and continuously learn from it accelerates the discovery of novel treatments and therapies, ultimately enhancing the quality of care for allergy sufferers and contributing to the advancement of allergy research 3 …”
Section: Figurementioning
confidence: 99%